Implementasi Sistem Daperma (PT. Pandai) Pembayaran Klaim Asuransi dalam Pelunasan Hutang Anggota Meninggal Dunia pada KSP Kopdit Obor Mas Cabang Pasar Tingkat - Hastuti N, Yuni; Sanga, Konstantinus Pati; Kurniawan, Antonius Philipus (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this study is to find out how the Implementation of the Daperma System (PT. Pandai) payment of insurance claims in repayment of debts of deceased members at KSP Kopdit Obor Mas Branch Pasar Level. To find out the problem of this research using qualitative descriptive methods, with data collection techniques using observation, interviews and documentation. From the results of this study, it can be concluded that in the event of repayment of debts of deceased members at KSP, the Obor Mas Kopdit is paid off based on loan insurance claims at Daperma (PT. PANDAI) if the claim is approved. In addition to getting loan repayment insurance, all deposits of deceased members will be returned to their heirs and receive compensation funds if during their lifetime the deceased member pays SSD and regularly pays mandatory deposits. Keywords: DAPERMA, Debt, Implementation, Insurance, KSP Kopdit Obor Mas.